Safety of scientific medical research is a State obligation - Marjolein Timmers; Mária Éva Földes (Health Economics, Policy and Law)
Conducting scientific medical research with human subjects presents risks that raise both ethical and human rights concerns. We argue in this article that applying a human rights framework to the problems that arise in the context of scientific medical research can contribute to a better understanding of the impact on individuals, the related obligations of the State, and the avenues to make the State accountable when things go wrong. We start our analysis with a case brought to the European Court of Human Rights, which we use as an illustration throughout the article. We then discuss the relevance of human rights to the field of scientific medical research with a focus on the right to life and the right to health. The article draws on international human rights jurisprudence that deals with concrete disputes arising from the clinical reality. We use case law to highlight the role of human rights law in tackling the real-life problems that may occur during scientific medical research. Our analysis contends that human rights law can provide valuable guidance for healthcare professionals and equip them to handle concrete situations in the clinical reality when the safety of research subjects is at stake.